1990
DOI: 10.1111/j.1471-6402.1990.tb00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Relationship Satisfaction in Lesbian Couples

Abstract: This study broadens the construct of intimate relationships to include the experience of lesbian couples. Various psychological variables were assessed in both partners of 275 lesbian couples who considered themselves to be dual career. Because of the paucity of information on lesbian relationships in the literature, considerable attention is first given to describing this sizable sample. Individual and couple scores on each variable were correlated with relationship satisfaction scores. Among individuals, rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
67
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 18 publications
11
67
3
Order By: Relevance
“…Moses (1978) found that fewer than one quarter of the lesbians studied "can be said to have 'come out' to most of the people they know" (p. 62). Twelve years later, Eldridge and Gilbert (1990) found comparable percentages: Three quarters of their sample had not disclosed their lesbian identity to the world at large (p. 57). Potter & Darty (1981) describe lesbians as an "almost invisible segment of American society" (p. 187), while Ponse (1976) notes that "heterosexual assumption" is an important feature of social interaction: " [It] means simply that parties to any interaction are presumed to be heterosexual unless demonstrated to be otherwise" (p. 317).…”
Section: Tara Healysupporting
confidence: 64%
“…Moses (1978) found that fewer than one quarter of the lesbians studied "can be said to have 'come out' to most of the people they know" (p. 62). Twelve years later, Eldridge and Gilbert (1990) found comparable percentages: Three quarters of their sample had not disclosed their lesbian identity to the world at large (p. 57). Potter & Darty (1981) describe lesbians as an "almost invisible segment of American society" (p. 187), while Ponse (1976) notes that "heterosexual assumption" is an important feature of social interaction: " [It] means simply that parties to any interaction are presumed to be heterosexual unless demonstrated to be otherwise" (p. 317).…”
Section: Tara Healysupporting
confidence: 64%
“…Consistent with previous research that found no relationship between demographic variables and ratings of relationship satisfaction or equality discrepancy among lesbians (Eldridge and Gilbert 1990;Kurdek and Schmitt 1986;Peplau et al 1982), this study found neither differences in age or income nor presence of children contributed to women's ratings of equality or satisfaction. This finding suggests that women in same-sex relationships may find ways to manage these differences without resulting in felt inequality in the relationships, and that having children may not challenge equality in women's same-sex relationships in the same way as in heterosexual relationships due to the doubling of female gender socialization in women's couples (Kurdek 2003).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, lesbian women experienced globally more positive affect during sexual activity, when compared to heterosexual women. Although no empirical evidence was found to support these findings, we may hypothesize that this tendency to observe higher levels of positive affect during sexual activity in the lesbian sample is associated with the high levels of sexual satisfaction and greater emotional intimacy experienced by lesbian couples (Cohen, Byers, & Walsh, 2008;Eldridge & Gilbert, 1990).…”
Section: Discussionmentioning
confidence: 51%